PENGARUH TEKNIK RELAKSASI AUTOGENIK TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI - Syapitri, Henny; Sinurat, Lasma Rina Efrina; Marbun, Agnes Silvina; Yulisma, Raudha (Jurnal Online Keperawatan Indonesia, 2025)
Worldwide, hypertension is on the rise, with the World Health Organization (WHO) projecting that by 2025, 29% of individuals would have the condition.  Presently, worldwide efforts to improve health are focusing on hypertension as a non-communicable illness.  The autogenic relaxation method is one non-pharmacological option for managing blood pressure.  The purpose of this research is to determine if hypertensive individuals' blood pressure may be reduced using the autogenic approach.  The researchers used a pretest-posttest control group design, making this study quasi-experimental.  One hundred forty-one hypertension patients who were seen at the Pante Raya Community Health Center made up the study's population.  Using a purposive sampling approach, the research comprised 40 participants as samples.  Seven days in a row, for a total of fifteen minutes per session, the autogenic relaxation method was given.  Using a digital sphygmomanometer, the patient's blood pressure was monitored.  The data was evaluated using a dependent t-test to compare the pre- and post-autogenic blood pressure levels, and an independent t-test to compare the intervention group's and control group's blood pressure levels.  Both the pre- and post-autogenic relaxation systolic and diastolic blood pressures were found to be significantly lower (p < 0.05).  This research found that hypertension individuals whose blood pressure was significantly reduced by using autogenic relaxation methods.  Thus, autogenic approaches provide a non-pharmacological approach to managing blood pressure that is both effective and safe.